Tracheomalacia Treatment Using a Large-Diameter, Custom-Made Airway Stent in a Case with Mounier-Kuhn Syndrome - Cengiz Özdemir; Sinem Nedime Sökücü; Levent Karasulu; Sedat Altın; Levent Dalar (Case Reports in Pulmonology)
Mounier-Kuhn Syndrome (MKS) is a rare congenital disease that presents with abnormal enlargement in the central airways. In MKS, tracheomegaly is accompanied by difficulty in expelling recurrent lung infections and bronchiectasia. We presented a patient with MKS where commercially made stents were inadequate for stabilization and a custom-made, self-expandable metallic stent with a diameter of 28 mm and length of 100 mm was used. Chest pain that was thought to develop due to the stent and that disappeared after stent removal may be considered the main complication leading to stent removal. Continuous positive airway pressure therapy (CPAP) therapy was planned for the control of symptoms, which re-emerged after stent removal. This case is presented as an example that complications developing due to the stent as well as patient noncompliance may lead to stent removal, even when useful results are obtained from treatment of MKS.